Vocational education and training (VET) system governance: a systematic literature review - Mende, Christian [Verfasser]; Oswald-Egg, Maria Esther [Verfasser]; Caves, Katherine [Verfasser] (My University, 2025)
“In this study, we conduct a systematic literature review of records across disciplines dealing with VET system governance. The literature draws on a broad array of disciplines including political science, sociology, economics, development economics, and education policy. Despite this, we find a generally interconnected literature, which is neither ideologically isolated nor always based in a single disciplinary approach. In addition, we identify 16 variables across 6 dimensions that are commonly used to describe governance in VET systems. Those dimensions are: codified, unified, and principled national approach; coordination at all levels; cooperation and involvement; skills supply and demand; finances and funding; and providing high-quality and attractive VET. In general, the literature is not fully cohesive but avoids being isolated into ideological silos.” (authors’ abstract; BIBB-Doku)
Keywords: T 4 Bezugswissenschaften; T 1 Forschungsrichtungen; S 4.3 Steuerung; 370; Wissenschaftsdisziplin; Interdisziplinarität; Berufsbildungsforschung; Governance; Literaturanalyse